2022
DOI: 10.1016/j.jgr.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Panax ginseng and ginsenosides on oxidative stress and cardiovascular diseases: pharmacological and therapeutic roles

Abstract: Traditionally, Asian ginseng or Korean ginseng, Pana x ginseng has long been used in Korea and China to treat various diseases. The main active components of Panax ginseng is ginsenoside, which is known to have various pharmacological treatment effects such as antioxidant, vascular easing, anti-allergic, anti-inflammatory, anti-diabetes, and anticancer. Most reactive oxygen species (ROS) cause chronic diseases such as myocardial symptoms and cause fatal oxidative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 74 publications
0
46
0
Order By: Relevance
“…According to the manufacturing processing technique of ginseng, Panax ginseng can be divided into three types: white ginseng, red ginseng, and black ginseng ( Hyun et al, 2022 ). White ginseng is produced by dehydration in the sun without cooking, and red ginseng is steamed at 90–100°C for 2–3 h. Until now, red ginseng is mainly processed in Korea, which is also named Korea red ginseng (KRG).…”
Section: Neuroprotective Effects Of Ginseng and Ginsenosides In Ische...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the manufacturing processing technique of ginseng, Panax ginseng can be divided into three types: white ginseng, red ginseng, and black ginseng ( Hyun et al, 2022 ). White ginseng is produced by dehydration in the sun without cooking, and red ginseng is steamed at 90–100°C for 2–3 h. Until now, red ginseng is mainly processed in Korea, which is also named Korea red ginseng (KRG).…”
Section: Neuroprotective Effects Of Ginseng and Ginsenosides In Ische...mentioning
confidence: 99%
“…and minor ginsenosides (Rh1, Rh2, Rg3, Rg5, etc.) ( Hyun et al, 2022 ). According to the chemical structures, ginsenosides can be divided into protopanaxadiol (PPD), protopanaxatriol (PPT), and oleanolic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The roots, leaves, and fruits of ginseng plants have been extensively used as herbal medicines. The antioxidant activity of ginseng is exploited to treat cardiovascular diseases ( Hyun et al, 2022 ). Interestingly, red ginseng has better antioxidant activity and is used to treat neurodegenerative diseases, gastroenteritis, liver damage, diabetes, and aging ( Lee et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that ginsenosides, the main active components in ginseng, have a positive effect on delaying aging and can effectively improve age-related cardiovascular disease, neurodegenerative diseases such as Parkinson’s disease and Alzheimer’s disease, as well as tumors ( Tangrodchanapong et al, 2020 ). These actions are closely related to their anti-inflammatory and anti-oxidant effects and effects on mitochondrial homeostasis ( Hyun et al, 2022 ). Therefore, ginsenosides have the potential to be used as an alternative natural medicine for anti-aging and life-prolonging effects.…”
Section: Introductionmentioning
confidence: 99%